Some factors affecting imitation nature of imitative stimulus, verbalization and sex of subject.[article]. - Adversario, Peñafrancia L.
Children tend to be quick in imitating certain types of behavior and slow in learning others. Just what type of behaviors are easily imitated by children, however, is still a big question mark to parents and educators alike. With boys and girls of ages five to six as subjects, the author in this study seeks to find out whether aggressive behavior is more readily imitated than the socially acceptable behavior of altruism. She also investigated the effect of the model's verbalization of certain details of his actions on the learning of both types of imitative responses. An analysis of Variance and a subsequent Duncan's Multiple Range Test show that socially acceptable responses are more easily learned than aggressive behaviors as evidenced by shorter reaction time and more accurate imitative responses. Verbalization is also seen to have a facilitative effect on limitations, However, when children are called upon to imitate aggressive behavior, it does not seem to matter whether models verbalize their aggression or not, No sex difference is reported in the study.